2001
DOI: 10.1038/sj.leu.2402027
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 expression in poor-risk acute myeloid leukemia with partial or complete monosomy 7

Abstract: Expression of the multidrug resistance (MDR1) phenotype, encoded by the MDR1 gene, is an adverse prognostic factor for CR and survival in acute myeloid leukemia (AML). Other prognostic factors, such as specific cytogenetic abnormalities, have been identified in AML. We have investigated the expression of the MDR1 gene in untreated AML patients with monosomy 7 (n = 12), and partial deletions (n = 7) of the long arm of chromosome 7 (respectively −7/7q−), because of the extremely bad prognosis associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…However, as expected, blast phase patients with loss of chromosomal material on 7q showed poor survival, because this is known to be predictive for rapid progression and poor response in AML therapy. [35][36][37] MPN-blast phase patients with cytogenetically undetectable 7qCNN-LOH had comparable survival rates to those with Ϫ7/7qϪ in their leukemic cells, which is in accordance with previously published data. 44 In addition, 9pCNN-LOH with homozygous JAK2 mutation was also linked to an inferior outcome in MPN-blast crisis in comparison with patients with either heterozygous JAK2V617F or wild-type JAK2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, as expected, blast phase patients with loss of chromosomal material on 7q showed poor survival, because this is known to be predictive for rapid progression and poor response in AML therapy. [35][36][37] MPN-blast phase patients with cytogenetically undetectable 7qCNN-LOH had comparable survival rates to those with Ϫ7/7qϪ in their leukemic cells, which is in accordance with previously published data. 44 In addition, 9pCNN-LOH with homozygous JAK2 mutation was also linked to an inferior outcome in MPN-blast crisis in comparison with patients with either heterozygous JAK2V617F or wild-type JAK2.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormalities involving chromosome 7 are frequently detectable in de novo and secondary AML, [34][35][36][37] and preceding studies have found a critical breakpoint region involving a locus at centromeric band 7q22, whereas the telomeric breakpoint varies from q32 to q36. Interestingly, the minimal deleted region in our cohort was located at 7q22.1 encompassing only 2 promising target genes, SH2B2 (previously named APS) and CUTL1.…”
Section: Discussionmentioning
confidence: 92%
“…MDR1 did not correlate with a lower induction rate in relapsed or refractory childhood acute myeloid leukemia [110]. Mechanisms other than MDR1 are responsible for the poor prognosis in monosomy 7 patients [111].…”
Section: No Impact Of Mdr1/pgp Expressionmentioning
confidence: 83%
“…MDR is the major complication and a formidable obstacle in the therapy of AL (6). Certain previous studies that used cyclosporine and verapamil to reverse the MDR of AL were not practical in the clinic due to the side-effects.…”
Section: Discussionmentioning
confidence: 99%